Association between dexmedetomidine sedation and mortality in critically ill patients with ischaemic stroke: a retrospective study based on MIMIC-IV database - Jun Zhang; Yuecheng Yang; Yunkui Zhang; Jingying Zhang; Haoyuan Wang (BMJ Open, 2025)
Objective This study investigates the effects of dexmedetomidine on short-term and long-term survival rates in intensive care unit (ICU) patients with ischaemic stroke.Design This is a retrospective study.Setting Data were sourced from the Medical Information Mart for Intensive Care IV database.Participants This study analysed 2816 patients with ischaemic stroke from the US Intensive Care database.Interventions Dexmedetomidine administration during the ICU stay was defined as the exposure.Methods Patients were categorised into the dexmedetomidine group and the control group. Cox regression analysis was used to identify factors that may influence the 28-day mortality rate of patients with ischaemic stroke. High-risk factors were incorporated as covariates, and a 1:1 propensity score matching using the logit model was constructed to compare the prognosis between the two groups.Primary and secondary outcome measures The primary outcome was 28-day mortality. The secondary outcomes included in-hospital mortality, ICU length of stay, hospital length of stay, mechanical ventilation duration and 180-day mortality in discharged patients.Results A total of 2816 patients were included. Cox regression analysis revealed that dexmedetomidine use was associated with a reduced risk of 28-day mortality. Following propensity score matching, each group comprised 407 patients. Dexmedetomidine was found to improve 28-day mortality (27.8% vs 36.6%, p=0.007). However, it was also associated with the prolonged length of hospital and ICU stay (p=0.002). Among discharged patients, dexmedetomidine use was also associated with an improved 180-day mortality rate (p=0.0019).Conclusion The use of dexmedetomidine is associated with improved short-term and long-term prognosis in patients with ischaemic stroke and could potentially confer benefits in those receiving mechanical ventilation.